Synthesis, Photophysical properties and OFET application of thienothiophene and benzothiadiazole based Donor-π-Acceptor-π (D-π -A-π) type conjugated polymers. (13th June 2023) - Ozturk, Serra E.; Isci, Recep; Faraji, Sheida; Sütay, Berkay; Majewski, Leszek A.; Ozturk, Turan
Graphical abstract: Highlights: D- π -A- π type TT and BT based polymers possessing various functional groups. Mega Stokes shift of 130 nm. A high OFET performance of the smallest subthreshold swing, SS, 250 mV dec -1 and 10 3 On/Off current ratio. Effects of electron donating/withdrawing (–CN, -F, -N(CH3 )2 ) substituents on device performances of the polymers. Abstract: Novel conjugated donor- π -acceptor- π (D- π -A- π) type polymers ( P 1- P 3 ), possessing thieno[3, 2- b ]thiophene (TT) with different aromatic substituents as donors, benzo[1–3] thiadiazole (BT) as an acceptor and thiophene as a π -linker, were designed and synthesized via palladium-catalyzed Stille coupling reaction. Their electronic, optical and thermal properties were investigated using UV–vis and fluorescence spectroscopies, cylic voltammetry, and thermal gravimetric analysis. Photophysical characterizations of these novel polymers showed a remarkable mega Stokes shift, reaching up to 130 nm and optic/electronic band gaps between 1.70 and 2.00 eV, as well as good thermal stability of degradation temperature at around 260 °C. To study the effect of electron donating and withdrawing groups on the electronic properties of the π -extended polymers, their organic field-effect transistors (OFETs) were fabricated and charge transport characteristics were investigated. While all three polymers showed a p-type field-effect behaviour, dimethylamine substituted P 3 exhibited the highest average saturated hole mobility, μsat, 0.04 cm 2 V −1 s −1, on/off current ratio, Ion /Ioff  = 3.0 × 10 3, and the smallest subthreshold swing, SS, 250 mV dec -1, outperforming similar p-type D- π -A- π semiconducting polymers reported in the literature. The results presented in this work corroborate that the three novel TT-BT polymers have promising potential for electronic and optoelectronic applications, in particular where the tunability of field-effect behaviour is essential for performance.